A matched-pair analysis comparing systematic prostate biopsy by conventional transrectal ultrasound-guidance versus software-based predefined 3D-guidance - Derigs, Fabian; Kowalewski, Karl-Friedrich; Hartung, Friedrich; Waldbillig, Frank; Neuberger, Manuel; Hardenberg, Jost von; Westhoff, Niklas Christian (Urology, 2023)
Objective - To compare software-based three-dimensional-guided systematic prostate biopsy (3D-GSB) with conventional transrectal ultrasound-guided systematic biopsy (TGSB) regarding prostate cancer (PCa) detection rates (CDR). - Methods - In total, 956 patients (200 TGSB patients and 756 3D-GSB patients) without prior positive biopsies and with a prostate-specific antigen value ≤20 ng/ml were eligible for analysis. TGSB and 3D-GSB cases were matched in a 1:1 ratio using propensity score matching with age, prostate-specific antigen, prostate volume, previous biopsy status, and suspicious palpatory finding as confounders. 3D-GSB was conducted with the semi-robotic prostate fusion-biopsy system Artemis. For each patient in both groups, SB was conducted in a similar pattern with 12 cores. All cores in 3D-GSB were automatically planned and mapped on a 3D-model as well as on the real-time transrectal ultrasound imaging. Primary end points were the clinically significant (cs) and overall CDR. Secondary end point was the cancer-positive core rate. - Results - After matching, the csCDR was not significantly different between the 3D-GSB and the TGSB groups (33.3% vs 28.8%, P = .385). Overall CDR was significantly higher for 3D-GSB compared to TGSB (55.6% vs 39.9%, P = .002). 3D-GSB detected significantly more non-significant PCa than TGSB (22.2% vs 11.1%, P = .004). In patients with PCa, the number of cancer-positive SB cores was significantly higher by TGSB (42% vs 25%, P < .001). - Conclusion - 3D-GSB was associated with a higher CDR than TGSB. However, no significant difference was shown in detection of csPCa between both techniques. Therefore, currently, 3D-GSB does not appear to add value to conventional TGSB.